Transdermal testosterone replacement therapy in men - Ullah MI; Riche DM; Koch CA (Dove Medical Press, 2014)
M Iftekhar Ullah,1 Daniel M Riche,1,2 Christian A Koch1,31Department of Medicine, University of Mississippi Medical Center, 2Department of Pharmacy Practice, The University of Mississippi, 3GV (Sonny) Montgomery VA Medical Center, Jackson, MS, USAAbstract: Androgen deficiency syndrome in men is a frequently diagnosed condition associated with clinical symptoms including fatigue, decreased libido, erectile dysfunction, and metabolic syndrome. Serum testosterone concentrations decline steadily with age. The prevalence of androgen deficiency syndrome in men varies depending on the age group, known and unknown comorbidities, and the respective study group. Reported prevalence rates may be underestimated, as not every man with symptoms of androgen deficiency seeks treatment. Additionally, men reporting symptoms of androgen deficiency may not be correctly diagnosed due to the vagueness of the symptom quality. The treatment of androgen deficiency syndrome or male hypogonadism may sometimes be difficult due to various reasons. There is no consensus as to when to start treating a respective man or with regards to the best treatment option for an individual patient. There is also lack of familiarity with treatment options among general practitioners. The formulations currently available on the market are generally expensive and dose adjustment protocols for each differ. All these factors add to the complexity of testosterone replacement therapy. In this article we will discuss the general indications of transdermal testosterone replacement therapy, available formulations, dosage, application sites, and recommended titration schedule.Keywords: hypogonadism, transdermal, testosterone, sexual function, testosterone replacement therapy, estradiol